Brief Report: Factors Released by Megakaryocytes Thrombin Cleave Osteopontin to Negatively Regulate Hematopoietic Stem Cells. (15th May 2015) - Storan, Melonie J.; Heazlewood, Shen Y.; Heazlewood, Chad K.; Haylock, David N.; Alexander, Warren S.; Neaves, Rebecca J.; Oteiza, Ana; Nilsson, Susan K.
Abstract Factor V (FV) and factor X (FX) activate and complex to form prothrombinase which subsequently cleaves prothrombin (PT), converting it to active thrombin. Thrombin cleaved osteopontin (tcOPN) contains a cryptic binding site for α4β1 and α9β1 integrins. We have previously shown that hematopoietic stem cells (HSC) bind to tcOPN via this site resulting in a decrease in their proliferation and differentiation. Therefore, tcOPN and the factors required for its generation are important components of the HSC niche. Herein we show mature megakaryocytes (MM, ≥8N) contain FV, FX, and PT mRNA and protein. Furthermore, we show 8N, 16N, 32N, and 64N MM all release the required factors to enable thrombin cleavage of OPN. Importantly, mice devoid of the myeloproliferative leukemia protein (Mpl), c‐Mpl−/− mice, contain only approximately 10% of normal megakaryocyte numbers, showed significantly reduced FX and tcOPN protein levels in endosteal bone marrow (BM). In addition, WT hematopoietic progenitors and HSC showed reduced homing to the BM of c‐Mpl−/− mice. This is the first report identifying MM as a key cellular component in the production of tcOPN in situ, allowing the BM microenvironment to self regulate HSC biology via tcOPN. Stem Cells 2015;33:2351–2357